Development of Antimicrobial Stewardship Programmes in Low and Middle-Income Countries: A Mixed-Methods Study in Nigerian Hospitals - Eneyi E. Kpokiri; David G. Taylor; Felicity J. Smith (MDPI AG, 2020)
Antimicrobial resistance (AMR) is a major concern facing global health today, with the greatest impact in developing countries where the burden of infectious diseases is much higher. The inappropriate prescribing and use of antibiotics are contributory factors to increasing antibiotic resistance. Antimicrobial stewardship programmes (AMS) are implemented to optimise use and promote behavioural change in the use of antimicrobials. AMS programmes have been widely employed and proven to improve antibiotic use in many high-income settings. However, strategies to contain antimicrobial resistance have yet to be successfully implemented in low-resource settings. A recent toolkit for AMS in low- and middle-income countries by the World Health Organisation (WHO) recognizes the importance of local context in the development of AMS programmes. This study employed a bottom-up approach to identify important local determinants of antimicrobial prescribing practices in a low-middle income setting, to inform the development of a local AMS programme. Analysis of prescribing practices and interviews with prescribers highlighted priorities for AMS, which include increasing awareness of antibiotic resistance, development and maintenance of guidelines for antibiotic use, monitoring and surveillance of antibiotic use, ensuring the quality of low-cost generic medicines, and improved laboratory services. The application of an established theoretical model for behaviour change guided the development of specific proposals for AMS. Finally, in a consultation with stakeholders, the feasibility of the plan was explored along with strategies for its implementation. This project provides an example of the design, and proposal for implementation of an AMS plan to improve antibiotic use in hospitals in low-middle income settings.